Arquitetura baseada em web e IoT para avaliação de desempenho de painéis fotovoltaicos - Bonfim, Christian Griehl (2025)
The performance of photovoltaic panels is traditionally evaluated using the currentvoltage (I-V) curve, an essential parameter for identifying defects and determining corrective actions, such as cleaning the panels or replacing damaged modules. Unlike simply measuring the short-circuit current and open-circuit voltage (which can be obtained with a multimeter and clamp meter), a complete I-V curve analysis verifies whether the panel is operating at its maximum productive potential. Despite its relevance, the use of I-V curve tracers is still uncommon, especially in smaller-scale systems like residential ones, due to the high cost of commercial equipment. To overcome this limitation, this work proposes the development of an automated, accessible, and scalable I-V curve tracer based on web and IoT technologies. The proposed architecture consists of three main modules: a web interface developed with React.js, an API implemented with Express.js, and a control device, represented by an ESP32 microcontroller. The operation follows this sequence: when accessing the web interface, the user can initiate the curve generation with a single command. This request is sent to the API, which publishes the command to start measurements to an MQTT broker. Upon receiving the command from the broker, the ESP32 controls a virtual electronic load, varying the duty cycle of a PWM signal from 100% down to 0% and performing the necessary current and voltage readings to compose the curve. As the project's focus is on software development, there is no physical hardware implementation for real measurements. Instead, the system consults predefined values, returning them as real-time current and voltage measurements. This simulation represents the resistance variation from short-circuit to open-circuit, allowing the entire characteristic curve of the panel to be traversed. Additionally, the ESP32 simulates a closed-loop temperature control, aiming to reach a panel temperature of 25 °C (the standard condition for efficiency measurements).During the PWM variation, the current and voltage data are sent to the MQTT broker and then forwarded by the API to the web interface, which processes and presents the final I-V curve graph to the user. The obtained results indicate that the proposed solution is a viable alternative for studies and development, with the potential for integration into remote monitoring systems and a relevant contribution to the field of renewable energy by combining modern web technologies with precision embedded control.